One of the possible mechanisms of glucose absorption slowing during immobilization stress - L. I. Korytov (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
An experimental study was performed on outbred male rats. In the first series of chronic experiments we studied the process of glucose absorption in an isolated loop of a jejunum in 12 rats. In the second series we studied the changes of lipid peroxidation during immobilization with the introduction of MFB and without in 18 rats in each group. Rats were operated in a special way. During all the days of immobilization there is an increased DK in serum of rats, reaching maximum on the seventh day of daily one hour immobilization. Lipid peroxidation products (conjugated dienes, malonicdialdehyde) and antioxidant activity of serum in chronic immobilization stress (1 hour a day during 7 days) and glucose absorption in a jejunum were investigated. Activation of lipid peroxidation (LPO) and its correlation with inhibition of glucose absorption rate were revealed. 2-ethyl-6-methyl- 3-hydroxypyridine succinate (EMHPS) administration of a 10 mg/kg a day dose for 7 days resulted in primary and end lipid peroxidation product decrease and increase in blood serum antioxidant activity. Under EMHPS correction, the glucose absorption rate approached the control group level in chronic immobilization stress. Activation of lipid peroxidation was suggested as one of the possible mechanisms of glucose absorption reduction during stress. Activation of the POL can be one of the decline reasons of the glucose absorption process during stress.